Impact of phosphorus deficiency on the interaction between the biofertilizer strain Serratia sp. S119 with peanut (Arachis hypogaeae L.) and maize (Zea mays L.) plants - Ludueña, Liliana Mercedes (2023)
The objective of this study was to evaluate the impact of phosphorus deficiency in the interaction between the biofertilizer Serratia sp. S119 strain and peanut and maize plants. Plant assays were performed under P deficiency and several parameters of plant-bacterial interaction were measured. Bacterial chemotaxis, root colonization and biofilm production were measured as the first steps of the plant-bacteria interaction. Also, the effect of root exudates of plants grown in P deficiency on the ability to solubilize insoluble phosphate of Serratia sp. S119 was analyzed. Results were further correlated with analyzes of the pqqE gene expression and the measurement of the activity of pqq promoter. Finally, the effect of the root exudates on the ACC deaminase activity of S119 strain was measured. Results indicated that plant root exudates obtained under P-deficient conditions positively attract Serratia sp. S119 and stimulate its colonization and biofilm formation. These plant root compounds showed also to produce a stimulating effect of the phosphate solubilization ability and ACC deaminase activity of S119 strain. Finally, root exudates obtained under P-deficient conditions induce pqqE gene expression and the activity of pqq promoter of S119 strain. In conclusion, root exudates contain specific signal molecules that attract phosphate solubilizing bacteria to the rhizosphere of peanut and maize plants growing in P deficient condition. Signal molecules would favor the colonization and establishment of the PSB strain in the surface tissues as well as in inner tissues, stimulate phosphate solubilization ability and enhance ACC deaminase activity to decrease plant’s nutritional stress response.